2016
DOI: 10.1073/pnas.1610437113
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from mixed hydrate nucleation for a funnel model of crystallization

Abstract: The molecular-level details of crystallization remain unclear for many systems. Previous work has speculated on the phenomenological similarities between molecular crystallization and protein folding. Here we demonstrate that molecular crystallization can involve funnel-shaped potential energy landscapes through a detailed analysis of mixed gas hydrate nucleation, a prototypical multicomponent crystallization process. Through this, we contribute both: (i) a powerful conceptual framework for exploring and ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 49 publications
6
70
0
Order By: Relevance
“…37 Previous work has demonstrated that these cages are important to the early-stage formation of CH4, H2S, and mixed CH4/H2S hydrates. [38][39][40][41][42][43] As can be seen in Fig Fig. 3A to Fig.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…37 Previous work has demonstrated that these cages are important to the early-stage formation of CH4, H2S, and mixed CH4/H2S hydrates. [38][39][40][41][42][43] As can be seen in Fig Fig. 3A to Fig.…”
Section: Resultsmentioning
confidence: 79%
“…These structurally-biased dynamics are consistent with recent work probing the rugged funnel-shaped potential-energy landscapes associated with crystal nucleation. 43 During nucleation in a liquid, a system progresses from an initial high-energy, highentropy liquid state (i.e., the broad mouth of the funnel) to a low-energy, low-entropy crystalline state (i.e., its narrow bottom). Since the landscape is locally rugged with local minima and maxima, the system must navigate according to its thermal energy as it descends further into the funnel.…”
Section: (See Section 13 In Si)mentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, the diffusion mechanism of guest molecules changes from more Brownian-like motion in the liquid phase to hopping-like behavior more consistent with a solid phase. 34,35 Using the funnel-shaped potential energy landscape for gas hydrate nucleation, 36 a system with high x g can be seen to approach the narrow neck region of its funnel-shaped energy landscape so that water cages can readily form and trigger hydrate nucleation. Addressing the question of ice nucleation is apparently more difficult than for gas hydrates at comparable undercooling, 36 the present results confirm that the presence of guest molecules in water does decrease the system entropy, and accordingly, the configurational space of the system (on its funnel-shaped energy landscape) is narrowed, so the system can more readily find a pathway to the solid phase.…”
mentioning
confidence: 99%
“…Multiple groups have studied hydrate formation with varying molecular models, ensembles and thermodynamic conditions [25]. The results from brute force simulations suggest hydrate formation occurs via a cooperative adsorption and growth mechanism between guest and host, and (despite some variability in resulting crystallinity) that the resulting post-critical solid structure at high driving force is generally amorphous while the resulting solid structure at lower driving forces is more crystalline, suggesting multiple drivingforce-dependent pathways [26][27][28][29][30][31]. Alternative methods to the brute force technique include the Forward Flux method [32], and metadynamics with restrained MD [33], employed by Lauricella et al, who suggested the main "pre-simulation" theories for the hydrate nucleation mechanism may all occur.…”
Section: Recent Simulationsmentioning
confidence: 99%